Implementasi Metode Pembiasaan Shalat Berjama’ah untuk Membentuk Karakter Religius dan Disiplin Siswa SMK dalam Pembelajaran PAI - Lutfiyatul Amaliyah, Eva Diana; Asdlori, Asdlori (Jurnal Pendidikan Agama Islam, 2025)
Character is a trait exists in a person that is related to God Almihjty, oneself, fellow human beings and the environment around them. Character can be formed in several ways, one of which is by getting used to praying in congregation, Getting used to praying in congregation can help students to have better character, especially religious character and disciplined character. This study aims to describe and analyze the implementation of the method of getting used to praying in congregation to form religious and disciplined character in students in Islamic Religious Education learning at State Vocational High School 1 Randudongkal Pemalang. Thr research method used is a case study with a gualititative approach. Data were collected through observation, interviewsa with Islamic religious education teachers and students and documentation of the implementation of the method getting used to praying in congregation. The subjects of the study werw Islamic Religious education teachers and students of State Vocational High Scool 1 Randudongkal Pemalang. The results of the study indicate that the implementation of the method habituation of congregational payer is effective in forming religious character and discipline of students in Islamic Religious Education learning. The habituation is carried out through several stages, namely planning, implementation and evaluation. The planning is thar create teaching modules, prayer schedules, imam, muezzin, and congregational prayer attendance. Implementation, the teacher invites students perform congregational prayers, delivers lectures that form religious character and discipline of students, in learning links Islamic Religious Educational material with prayer. The evaluation concuted by the Islamic Religioys Education teacher on the habit of praying in congregation by students is by observing students who perform congregational prayers in the mosque, observing changes in students attitudes when performing congregational prayers and observing students prayer attendance. This habit has a positive impact on changes in students character, such as obeying the commands of Allah SWT, getting closer to Allah SWT, being on time in perfoming prayer and obeying the rules that have been set.